Peacebuilding Strategies in Conflict Societies Through Art Education: Cyprus - Miralay, Fatma (2020)
The purpose of this study is to include the evaluation of teacher opinions concerning the acquisition of peace culture by students through art education  programs applied in Northern and Southern Cyprus. The study is patterned according to qualitative research method and is performed with focus group interview. The research included 10 secondary school (K12) 7th grade visual arts course teachers in total form both Northern Cypriot Turkish community (n=5) and Southern Cypriot Greek community (n=5). In the study, semi-structured interview form was used in obtaining the opinions of teachers. Teachers stated that they believed that acquisition of peace culture awareness by students through art education  which would result in individual and social peace. They also displayed that families had a very important role to play in the popularization of peace culture through art education and that school administration and ministries were determinant in this respect. In addition, teachers added that in both communities education institutions did not play their part adequately in the popularization of peace culture in education.